2005
DOI: 10.1021/jo0486692
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-Pot Synthesis of Some New Interesting Pyrrole Derivatives

Abstract: [reaction: see text] 11-(1H-Pyrrol-1-yl)-11H-indeno[1,2-b]quinoxaline and 3-(1H-pyrrol-1-yl)indolin-2-one derivatives have been synthesized in good yields in a novel, one-pot, and efficient process by condensation of 11H-indeno[1,2-b]quinoxalin-11-one or isatin derivatives with 4-hydroxyproline on solid-support montmorillonite K10 under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 15 publications
0
52
0
2
Order By: Relevance
“…32 The results obtained are in line with earlier studies by various prominent research groups which suggests that PA contains acidic properties possibly due to presence of alumina which makes it an interesting and effective catalyst for one pot conversion of mono-sugar conversion as compared to mineral acids, metals salts and zeolites. 33,34 In this regard, Yao-Bing Huang et al, have recently reported 100% conversion of LA and 99.4% methyl levulinate yield from Al 2 (SO 4 ) 3 at 110 C under microwave-irradiation.…”
Section: -31mentioning
confidence: 99%
“…32 The results obtained are in line with earlier studies by various prominent research groups which suggests that PA contains acidic properties possibly due to presence of alumina which makes it an interesting and effective catalyst for one pot conversion of mono-sugar conversion as compared to mineral acids, metals salts and zeolites. 33,34 In this regard, Yao-Bing Huang et al, have recently reported 100% conversion of LA and 99.4% methyl levulinate yield from Al 2 (SO 4 ) 3 at 110 C under microwave-irradiation.…”
Section: -31mentioning
confidence: 99%
“…13 The importance of these one-pot three component reactions in such synthesis has been demonstrated in the Mannich, Ugi, Biginell and aza-Baylish-Hillman reactions.…”
Section: -7mentioning
confidence: 99%
“…Alum (KAl(SO 4 ) 2 ×12H 2 O) has previously been reported to be effective in the synthesis of cis-isoquinolic acids (14), mono and disubstituted 2,3-dihydroquinazolin-4 (1H)-ones (15), dihydropyrimidine via Biginelli reaction (16), coumarins (17), 1,3,4-oxadiazoles (18), dibenzoxanthenes (19), 1,5-benzodiazepines (20), and trisubstituted imidazoles (21). Alum has continued to be exploited in organic synthesis because it is a non-toxic, inexpensive, eco-friendly, and easy handling catalyst.…”
Section: Introductionmentioning
confidence: 99%